Impact of electron–hole recombination mechanism on the photocatalytic performance of ZnO in water treatment: A review - Tuama, Alaa Nihad; H. Alzubaidi, Laith i; Jameel, Muhammad Hasnain; Abass, Khalid Haneen; Mayzan, Mohd Zul Hilmi; N. Salman, Zahraa (2024)
One of the most popular standard benchmark photocatalysts in the water treatment and environmental applications fields is zinc oxide (ZnO). Nevertheless, the total photocatalytic efficacy is limited by ZnO’s high band gap and the significant recombination of photogenerated charge carriers, particularly in its nano size. This can be further circumvented by hybridizing ZnO with a material that has a narrow band gap, such as metallic, non-metallic, carbon-based, or polymericbased, to change its electronic band structure and other pertinent features. The use of ZnO-based photocatalyst in wastewater treatment shows a lot of potential as an effective and long-lasting oxidation technique. To increase photocatalytic efficiency, ZnO photocatalysts can be prepared in a variety of ways and modified via doping. In the present review, we assess recent studies on the creation of ZnO-based photocatalysts for the treatment of water using a variety of preparation methods based on electron–hole generation and recombination. The majority of development strategies and research on attaining the best possible photocatalysis performance in high-yield degradation with related factors are discussed, and the primary reasons for increased efficiency are explained. We consider areas where ZnO-based photocatalysts for water treatment could be improved. Finally, there is also a discussion of the prospects and challenges in this exciting field. Our evaluation aims to assist researchers in creating photocatalysts for water treatment that are both affordable and highly effective.